(untitled) (The Journal of Interdisciplinary Human Studies, 2026)
This scientific article analyzes the philosophical foundations of values, major axiological schools, and modern approaches. Special attention is paid to the relationship between axiology and spirituality, the impact of globalization on the evolution of values, and the specific features of value-oriented approaches in Central Asia. The research findings contribute to a deeper understanding of the role of values in the spiritual development of society.